2020
DOI: 10.53761/1.17.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Shared learning objectives in interdisciplinary projects: Game design in a Sino-Scandinavian context

Abstract: The learning goals of project-based courses are typically specific for each involved discipline. Game development is deeply interdisciplinary and some of its core principles are shared across disciplines, from art to programming. This article presents a project-based approach where students majoring in arts and students majoring in technology share learning objectives. The course has been developed in a SinoScandinavian collaboration. Experiences from well-established Scandinavian game development programmes h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…Although this was an isolated account of the potential collaborative aspects of game audio, it indicates that sound design constitutes an important factor in the development process. However, current academic studies on game audio seem to provide somewhat isolated accounts of audio production, thus leaving out collaborative aspects (Engström, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although this was an isolated account of the potential collaborative aspects of game audio, it indicates that sound design constitutes an important factor in the development process. However, current academic studies on game audio seem to provide somewhat isolated accounts of audio production, thus leaving out collaborative aspects (Engström, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The research community has shown an increasing interest in digital games since the turn of the millennium (Martin, 2018). The interest in studying game development in general and “in the wild” (i.e., as it is conducted at the companies), has however been limited (Engström, 2020). Instead, research has primarily focused on isolated parts of the process, such as game design as a solitary task, or on specific technical challenges such as graphic rendering.…”
Section: Game Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of digital games requires a diversity of disciplines and professions working together, as shown by Wang and Nordmark (2015), and this is reflected in higher education in game development (Engström, Lyu, Backlund, Toftedahl, & Rosendahl Ehmsen, 2020). Students work on projects and demonstrate their knowledge by solving problems or building artefacts through co-creation within interdisciplinary setups (Ibid.).…”
Section: The Interconnections Of Disciplines Within Digital Gamesmentioning
confidence: 99%
“…A Aprendizagem Baseada em Projetos (ABP) e outras metodologias ativas surgem na primeira metade do século XX, mas passam a ser mais pesquisadas e aplicadas nos últimos 50 anos (Pasqualetto, 2017). Recentemente, também há um maior número de estudos e aplicações dessas metodologias ativas no contexto da computação por meio de ambientes mais interativos e agradáveis na percepção dos estudantes (Garneli et al, 2015;Engström et al, 2020). A ABP é comumente associada à teoria de aprendizagem construtivista pela origem comum, cujo pensamento gira em torno do estudante ser protagonista do próprio aprendizado (Ertmer & Newby, 2013).…”
Section: Introductionunclassified